Sickle Cell Anemia, the First Molecular Disease: Overview of Molecular Etiology, Pathophysiology, and Therapeutic Approaches - Martin H. Steinberg (The Scientific World Journal)
The root cause of sickle cell disease is a single β-globin gene mutation coding for the sickle β-hemoglobin chain. Sickle hemoglobin tetramers polymerize when deoxygenated, damaging the sickle erythrocyte. A multifaceted pathophysiology, triggered by erythrocyte injury induced by the sickle hemoglobin polymer, and encompassing more general cellular and tissue damage caused by hypoxia, oxidant damage, inflammation, abnormal intracellular interactions, and reduced nitric oxide bioavailability, sets off the events recognized clinically as sickle cell disease. This disease is a group of related disorders where sickle hemoglobin is the principal hemoglobin species. All have varying degrees of chronic hemolytic anemia, vasculopathy, vasoocclusive disease, acute and chronic organ damage, and shortened life span. Its complex pathophysiology, of which we have a reasonable understanding, provides multiple loci for potential therapeutic intervention.